Sequential impact of niobic and tantalic acid on the synthesis of their hexa- and decametalate isopolyanions - Rambaran, Mark A. (Dalton Transactions, 2025)
Polyoxometalates (POMs) and their instrinsic discrete nature has enabled them to support a wide range of research spanning solution-speciation chemistry, biological/medical assays, catalytic processes and fundamental crystallography. The structure-property relationship of POMs are a consequence of their constiuent metal atoms, which inevitably are formed under specific regimes - for simplicity, acidic or basic. Due to the ease of synthesis of the molybdenum and tungsten POMs, there has been relative ease in expanding their chemistry. Whereas syntheses of niobium and tantalum POMs has comparatively proven to be more challenging; albeit not often emphasised. The latter indicates the disparity in the advancement of the solution chemistry of niobium and tanlatum, compared to molybdenum and tungsten. This perspective highlights the crucial points - sequentially - in developing the hexa- and decametalate POM-syntheses of niobium (polyoxoniobates) and by extension tantalum (polyoxotantalates), which benefited improving our understanding of their respective solution chemistries.
Keywords: niobium; polyoxometalate; Tantalum; hexaniobate; decaniobate; hexatantalate